INTEGRASI ANALISIS SWOT, KONSEP 5 C DAN MAQOSHID SYARIAH DALAM PENERAPAN MANAJEMEN RESIKO DI BMT - Wahyu Hidayat (STES Islamic Village, 2019)
The objective of this paper is to explore the implementation of SWOT analysis, 5C analysis and maqoshid syariah analysis in order to manage the various risks in Islamic Microfinance in Indonesia particularly Baitulmaal wa Tamwil or Islamic Financial Service Cooperatives. Methode used in this studi is qualitative analysis with libarary reseach approach. The finding of this study is to manage many risks in Islamic Microfinance SWOT, 5C and Maqoshid Syariah could be use simultantly. The implementation of this various techniques will minimize the degree of risk in microfinance instutuions, particularly in BMT.